Robert R. Hitt papers - Hitt, Robert R. (Robert Roberts), 1834-1906.
Correspondence, diaries, notes and notebooks, business records, family papers, newspaper clippings, photographs, and other papers relating to Hitt's service as U.S. assistant secretary of state, U.S. congressman from Illinois, and secretary to the U.S. Legation in Paris, France. Also documents his service as court reporter, chairman of the U.S. House Committee on Foreign Affairs, and reporter for a board of treaty commissioners to the Indians in 1865. Includes shorthand notes of political events in Illinois between 1856 and 1860, in particular of speeches by Stephen A. Douglas, Abraham Lincoln, William Henry Seward, and Edwin McMasters Stanton; debates between Lyman Trumbull and William Allen and between Trumbull and Orlando B. Ficklin; and Democratic and Republican political meetings and conventions. Also includes a diary kept by Hitt in shorthand, 1857-1864, along with a transcription of the diary describing life in Chicago, Ill., especially the courts and the court appearances of Abraham Lincoln. Subjects include the 1858 Lincoln-Douglas debates in Illinois; the Holt-Davis Commission of 1861, led by Joseph Holt and David Davis, investigating John C. Fremont's activities in Missouri; U.S. War Department courts-martial during and after the Civil War; intervention in Cuba during the revolution, 1895-1898; the annexation of Hawaii, 1898; tariff; and Hitt's business affairs including banking, real estate, and the Louisville, New Albany & Chicago Railway. Hitt family papers include family histories, financial records, photographs, and other papers. Correspondents include Hitt's business agent, George Williams, of Lafayette, Ind.
U.S. representative from Illinois.
Collection material in English, with English shorthand.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allen, William, -- 1827-1881.; Davis, David, -- 1815-1886.; Douglas, Stephen A. -- 1813-1861.; Ficklin, Orlando B. -- 1808-1886.; Frémont, John Charles, -- 1813-1890.; Holt, Joseph, -- 1807-1894.; Lincoln, Abraham, -- 1809-1865.; Seward, William Henry, -- 1801-1872.; Stanton, Edwin McMasters, -- 1814-1869.; Trumbull, Lyman, -- 1813-1896.; Williams, George, -- active 1882-1894 -- Correspondence; Hitt family; United States. -- Congress. -- House; United States. -- Congress. -- House. -- Committee on Foreign Affairs; United States. -- Department of State; United States. -- Legation (France); United States. -- War Department; Democratic Party (U.S.); Louisville, New Albany & Chicago Railway; Republican Party (U.S. : 1854- ); Banks and banking -- United States; Business enterprises -- Indiana -- Lafayette; Campaign debates -- Illinois; Courts -- Illinois -- Chicago; Courts-martial and courts of inquiry -- United States; Diplomatic and consular service, American -- France; Indians of North America -- Treaties; Indians of North America -- Government relations; Law reporting -- Illinois -- Chicago; Lincoln-Douglas Debates, Ill., 1858.; Political conventions -- United States; Political parties -- United States; Railroads -- Illinois; Railroads -- Indiana; Railroads -- Kentucky; Real estate investment -- United States; Tariff -- United States; Chicago (Ill.) -- History; Cuba -- History -- Revolution, 1895-1898.; France -- Foreign relations -- United States; Hawaii -- Annexation to the United States; Hawaii -- History -- 1893-1900.; Illinois -- Politics and government -- 19th century; Missouri -- History -- Civil War, 1861-1865.; United States -- Foreign relations -- 1865-1921.; United States -- Foreign relations -- France; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1865-1933.; Representatives, U.S. Congress -- Illinois